Harnessing de novo transcriptome sequencing to identify and characterize genes regulating carbohydrate biosynthesis pathways in Salvia guaranitica L. - Abbas, Zahid Khorshid; Al-Huqail, Arwa Abdulkreem; Abdel Kawy, Aesha H.; Abdulhai, Rabab A.; Albalawi, Doha A.; AlShaqhaa, Manal Abdullah; Alsubeie, Moodi Saham; Darwish, Doaa Bahaa Eldin; Abdelhameed, Ahmed Ali; Soudy, Fathia A.; Makki, Rania M.; Aljabri, Maha; et al. (Frontiers in Plant Science, 2024)
Introduction Carbohydrate compounds serve multifaceted roles, from energy sources to stress protectants, found across diverse organisms including bacteria, fungi, and plants. Despite this broad importance, the molecular genetic framework underlying carbohydrate biosynthesis pathways, such as starch, sucrose, and glycolysis/gluconeogenesis in Salvia guaranitica, remains largely unexplored. Methods In this study, the Illumina-HiSeq 2500 platform was used to sequence the transcripts of S. guaranitica leaves, generating approximately 8.2 Gb of raw data. After filtering and removing adapter sequences, 38 million reads comprising 210 million high-quality nucleotide bases were obtained. De novo assembly resulted in 75,100 unigenes, which were annotated to establish a comprehensive database for investigating starch, sucrose, and glycolysis biosynthesis. Functional analyses of glucose-6-phosphate isomerase (SgGPI), trehalose-6-phosphate synthase/phosphatase (SgT6PS), and sucrose synthase (SgSUS) were performed using transgenic Arabidopsis thaliana. Results Among the unigenes, 410 were identified as putatively involved in these metabolic pathways, including 175 related to glycolysis/gluconeogenesis and 235 to starch and sucrose biosynthesis. Overexpression of SgGPI, SgT6PS, and SgSUS in transgenic A. thaliana enhanced leaf area, accelerated flower formation, and promoted overall growth compared to wild-type plants. Discussion These findings lay a foundation for understanding the roles of starch, sucrose, and glycolysis biosynthesis genes in S. guaranitica, offering insights into future metabolic engineering strategies for enhancing the production of valuable carbohydrate compounds in S. guaranitica or other plants.